PENGARUH INVESTASI PENDIDIKAN TERHADAP PERTUMBUHAN SISWA SEKOLAH DASAR - Elfitriani, Elfitriani; Ramanda, Fatma; Desyandri, Desyandri; Jamaris, Jamaris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on the fundamental education provided to students, which includes basic knowledge and character development. The knowledge taught by teachers in elementary school serves as an investment for students for the future, reaching higher levels of education. This study aims to understand the influence of educational investment on the growth of elementary school students. This type of research is descriptive qualitative research using the library research method. The data collection method involves gathering data through documentation studies in the form of books, journals, articles, and magazines relevant to education as an investment in human resources. The data analysis technique is conducted critically and in-depth to obtain results and draw conclusions. The results of the study show that education is viewed as an indirect form of investment because it will have a positive impact on the growth of students. The benefits of educational investment include acquiring knowledge; education is an essential element in student growth, equally important as other forms of investment. The growth of elementary school students with a good understanding of the educational investment conveyed by teachers will realize the importance of pursuing education.